Utilization of Maternal and Child Health Care Services and Nutritional Status of Under Five Children in Bungmati Village Development Committee, Lalitpur, Nepal - Bhandari, Buna; Shrestha, S (Birat Journal of Health Sciences, 2017)
Introduction Maternal and child health care services is essential component to promote family health. Despite of being provided free of cost, adequate utilization on of services is still the issue affecting health of both mother and child in Nepal. Objective The objective of this study was to assess the utilization of Maternal and child health care services and nutritional status of under five children in Bungmati Village Development Committee Lalitpur, Nepal Methodology Descriptive cross sectional study was conducted in Bungmati VDC of Lalitpur district, Nepal among one hundred and fifty households having either under five children, postnatal mothers or pregnant women which was selected purposively based on the objectives of the study. Data was collected by using interview guidelines and anthropometric measurement of children under five was taken. Collected data were analyzed in SPSS. Results Regarding utilization of maternal health care services, 90.9% had done their four-time antenatal checkup, 94.2% had delivered their baby at hospital and 65% married women of reproductive age were using one of the family planning methods. Likewise, immunization of under five children showed 100% BCG coverage, 88% pentavalent DPT and Polio, 77% Measles and low coverage of inject able Polio vaccine. About Nutritional status of under five children, more than half (57%) of the child were underweight, 41% were stunted and 20% of them were wasted. Conclusion Utilization of maternal health care services is good though Coverage of family planning needs to be improved and Immunization program should be strengthened. Awareness program for improvement of nutritional status of the under five children should be planned to address nutritional problem of children. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, page: 93-97